(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2024)
We question senses and meanings from “instructional material” in history teaching and explore its meanings (or the absence of it), with focus on History teaching and learning. We analyze how instructional materials have been used based on Brazilian History of Education researches. We develop some thoughts about production, propagation, and uses of instructional materials in their political and technological dimensions, and, at last, we propose five premises that could support their creation and analysis. We advocate that History teaching and learning materials should be inquiry based to propose multiple views, to provoke respect about diversity and critical thinking on inequalities. They should also mobilize different resources and knowledge, operate with concepts, and establish reflections about technologies used in the material itself.